A Multisite Study on Knowledge, Perceived Motivators, and Perceived Inhibitors to Precepting Nursing Students within the Clinical Environment in Ghana - Nancy Innocentia Ebu Enyan; Sarah Ama Amoo; Christian Makafui Boso; Patience Fakornam Doe; Dianne Slager (Hindawi Limited, 2021)
Background. Preceptorship constitutes an important component of the educational process of training nursing students. The purpose of this study was to assess the knowledge, perceived motivators, and perceived inhibitors to precepting nursing students at the clinical placement sites in the Cape Coast Metropolis of the Central Region of Ghana. Methods. A descriptive cross-sectional study was conducted among 442 nurses and midwives aged 27-56 years with at least three years of work experience. Data were collected with a questionnaire and analyzed using frequency counts, percentages, exploratory factor analysis, and point biserial correlation. Results. The results indicate that the participants had a high knowledge of preceptorship of up to 91.2% (n = 404). A significant proportion of up to 88.2% (n = 390) had an intention to precept nursing students in the near future. The three important perceived motivational factors to precepting nursing students were the learning and professional needs of students, helping students to develop skills, and experience and formal recognition of the role of preceptorship. The main perceived inhibitors to engage in a preceptorship role were lack of preparation for the role, lack of support from faculty and nurse managers, and additional work burden. The results further indicate a significant strong positive correlation between experience and professional recognition of preceptorship and the intention to precept nursing students in the near future (r = 0.99, p=0.037). Conclusions. The nurses and midwives who participated in the study are knowledgeable about preceptorship and have the intention to precept nursing students. Having enough experience on the job and being formally recognized as a preceptor may motivate these professionals to precept nursing students. However, there are critical perceived barriers that need to be addressed, to enable more nurses and midwives with the desire to precept students to engage in the preceptorship role.